Myopia - I Dewa Bagus Ketut Widya Pramana (Rifa'Institute, 2021)
Refractive disorder is the most common cause of visual impairment in the world, and one of them is myopia. Myopia is a condition of the eye failing to focus light from an object causes it to focus in front of the retina. The elongation of the axis of the eyeball and the high refractive power of the cornea and lens might be the cause of myopia. Myopic patients often complain of blurred vision when looking at a far objects. There are several risk factors of myopia, including genetics, gender, age and environment.This article is literature review. The purpose of this paper is to provide an overview related to refractive disorders, especially myopia. The management of myopia patients can be divided into 2, including optical therapy and pharmacological therapy. Optical therapy includes the smallest negative spherical glasses that provide maximum visual acuity, contact lenses, and orthokeratology. Management of myopic patients aims to reduce progression and complications by providing optical therapy in the form of spherical glasses, contact lenses, and orthokeratology